Multivariate Analysis of Pelagic Fishes in the South China Sea Area - Uddin, Md. Shahab (2001)
Pelagic fishes are important fisheries resources in the South China Sea Area. The aim of the study is to determine the dynamics and status of pelagic fishes and develop the fishery management efforts for sustainable development in the region Three analytical methods, correlation analysis, principal component analysis and cluster -:analysis were used for this purpose. In this study, 19 species groups were considered and annual catch data were collected from SEAFDEC Fishery Statistical Bul1etins from 1976 to 1996. For estimation of MSY (Maximum Sustainable Yield) in the East Coast of Peninsular Malaysia, Schaefer's Surplus Production Model was used based on catch and effort data. In the case study of estimation of MSY, the estimated MSY was 94,321 mt and fMSY was 74,011 (days/year) by fishing gear standardization. This study estimated MSY-like value of the whole South China Sea provisionally based on studies done in the East Coast of Peninsular Malaysia. The correlation analysis showed the relationship among 21 sub-areas on the basis of catch composition per year .The study indicated that Taiwan, Hong Kong and Singapore did not show significant relationship with other sub-areas. However, West Sumatra, South Java etc showed significant relationship with other sub-areas. The principal component analysis showed alternation of the major species groups in different sub-areas. The analysis indicated that alternation of major catches .. were observed at two or four years interval while some species groups were found to be stable over the periods in different sub-areas. Alternation of pelagics by sub-area and by species are very important information as the baseline data for multicountry's fisheries management. The cluster analysis was used for grouping of sub-areas on annual basis and overall basis. The results of overall basis are summarized in the following two types of grouping. The first type of grouping is as follows: (1) Taiwan, Indonesian part of Malacca Straits, West Coast of Peninsular Malaysia, East Sumatra and Kalimantan; (2) Luzon, Visayas, Mindanao, Sulewesi & Gulf of Thailand; (3) Hong Kong, West Sumatra, North java, South Java, Bali-Nusa Tenggara, Maluku-Irian Jaya, East Coast of Peninsular Malaysia, Sarawak, Sabah, Indian Ocean and Singapore. The second grouping is that, all sub-areas were grouped into six clusters: (1) Taiwan;(2) Gulf of Thailand; (3) East Coast of Peninsular Malaysia & North Java; (4) Indonesian part of Malacca Straits, West Coast of Peninsular Malaysia; East Sumatra & Kalimantan; (5) Luzon, Visayas, Mindanao & Sulawesi and (6) Hong Kong, West Sumatra, South Java, Bali-Nusa Tenggara, Maluku-Irian Jaya, Sarawak, Sabah, Indian Ocean & Singapore. On the pelagic resources or shared stocks, this study emphasized the importance of multi-country's fisheries management and that detailed information is required to achieve the objectives. This study identified the fisheries relationships among the sub-areas, and also clarified the alternation of pelagics in the South China Sea area, based on the multivariate analyses. The important baseline information obtained from the study can be utilised for multi country's pelagic fisheries management in the South China Sea area.